Public risk perception and behaviours towards COVID-19 during the first and second waves in Nigeria: a secondary data analysis. Issue 4 (1st April 2022) - Ochu, Chinwe Lucia; Onoja, Michael; Olatunji, David; Okusanya, Babasola O; Usuwa, Ifeoma Sophia; Akeju, David O; Disu, Yahya; Adejo, Samuel Ojima; Eziechina, Sunday; Nwiyi, Gloria; Okediran, James Olatunde; Elimian, Kelly Osezele; et al.
Abstract : Objectives: To describe changes in public risk perception and risky behaviours during the first wave (W1) and second wave (W2) of COVID-19 in Nigeria, associated factors and observed trend of the outbreak. Design: A secondary data analysis of cross-sectional telephone-based surveys conducted during the W1 and W2 of COVID-19 in Nigeria. Setting: Nigeria. Participants: Data from participants randomly selected from all states in Nigeria. Primary outcome: Risk perception for COVID-19 infection categorised as risk perceived and risk not perceived. Secondary outcome: Compliance to public health and social measures (PHSMs) categorised as compliant; non-compliant and indifferent. Analysis: Comparison of frequencies during both waves using χ 2 statistic to test for associations. Univariate and multivariate logistic regression analyses helped estimate the unadjusted and adjusted odds of risk perception of oneself contracting COVID-19. Level of statistical significance was set at p<0.05. Results: Triangulated datasets had a total of 6401 respondents, majority (49.5%) aged 25–35 years. Overall, 55.4% and 56.1% perceived themselves to be at risk of COVID-19 infection during the W1 and W2, respectively. A higher proportion of males than females perceived themselves to be at risk during the W1 (60.3% vs 50.3%, p<0.001) and the W2 (58.3% vs 52.6%, p<0.05). Residing in the south-west was associated with not perceiving oneself at risk of COVID-19 infection (W1—AOdds Ratio (AOR) 0.28; 95% CI 0.20 to 0.40; W2—AOR 0.71; 95% CI 0.52 to 0.97). There was significant increase in non-compliance to PHSMs in the W2 compared with W1. Non-compliance rate was higher among individuals who perceived themselves not to be at risk of getting infected (p<0.001). Conclusion: Risk communication and community engagement geared towards increasing risk perception of COVID-19 should be implemented, particularly among the identified population groups. This could increase adherence to PHSMs and potentially reduce the burden of COVID-19 in Nigeria.